2009
DOI: 10.1080/14634980903133757
|View full text |Cite
|
Sign up to set email alerts
|

Water pollution studies in the rivers of the Edirne Region–Turkey

Abstract: Physico-chemical parameters of Tunca, Merich, Arda and Ergene rivers, in the Edirne region of Turkey, were investigated. Studies were carried out during 1998–2004 and the data obtained were compared with EU threshold levels. The results showed that the total concentrations of P, Pb, Cu, Ni, Mn and Co were higher than these threshold levels. There is an urgent need for Turkey to limit water pollution from a wide range of dangerous substances, particularly at a time when it is being considered as an EU candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…The dramatic shift in CDOM optical signature directly downstream of the merging with Ergene, combined with the more than an order of magnitude increase in NH4+, the > 2‐fold increase in Cl − , and the twofold increase in DOC, highlighted the importance of the Ergene river as a major source of allocthonous inputs of carbon, nutrients, and pollutants in this system. This is consistent with Sakcali et al (), who compared water quality in the three major tributaries flowing into Ervos: the Ergene, the Tunca, and the Arda river (the last two merging with Evros upstream of our northernmost sampling site) and found particularly high pollution levels in the Ergene river. Water samples from Ergene had the highest sulfate and nitrogen concentrations, the lowest DO levels, and considerably higher biological (BOD) and chemical oxygen demand (COD) values (by more than a factor of 5) (Sakcali et al ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The dramatic shift in CDOM optical signature directly downstream of the merging with Ergene, combined with the more than an order of magnitude increase in NH4+, the > 2‐fold increase in Cl − , and the twofold increase in DOC, highlighted the importance of the Ergene river as a major source of allocthonous inputs of carbon, nutrients, and pollutants in this system. This is consistent with Sakcali et al (), who compared water quality in the three major tributaries flowing into Ervos: the Ergene, the Tunca, and the Arda river (the last two merging with Evros upstream of our northernmost sampling site) and found particularly high pollution levels in the Ergene river. Water samples from Ergene had the highest sulfate and nitrogen concentrations, the lowest DO levels, and considerably higher biological (BOD) and chemical oxygen demand (COD) values (by more than a factor of 5) (Sakcali et al ).…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with Sakcali et al (), who compared water quality in the three major tributaries flowing into Ervos: the Ergene, the Tunca, and the Arda river (the last two merging with Evros upstream of our northernmost sampling site) and found particularly high pollution levels in the Ergene river. Water samples from Ergene had the highest sulfate and nitrogen concentrations, the lowest DO levels, and considerably higher biological (BOD) and chemical oxygen demand (COD) values (by more than a factor of 5) (Sakcali et al ).…”
Section: Discussionsupporting
confidence: 93%
“…However, average lowest values of Al, B, Cd, Cu, Ni, and Pb are within normal limits (Between Class II and III) ( Table 5). Sakcali et al [9], have reported anomalies in metal concentrations and have related this to sources such as landfill leaching and municipal and industrial discharges in Meric, Arda, Tunca, and Ergene Rivers in Turkey. The same sources could be the reason of this high level of heavy metal pollution in Riva Stream.…”
Section: Parametersmentioning
confidence: 97%
“…Heavy metals cause pollution in the aquatic systems by atmospheric deposition, erosion of geological matrix and anthropogenic activities such as industrial effluents, domestic sewage, and mining wastes [8][9][10]. Rivers, which feed lakes and seas, are very important water suppliers in freshwater systems.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in this region have demonstrated high concentrations of heavy metals in its water, sediment, soil, air, plants, and animals, and even among its human inhabitants. [13][14][15][16] We report, moreover, the review of relevant literature.…”
Section: Figure 1 Ergene-evros-ardas River Basinmentioning
confidence: 99%